Optimisation of Inductors in Power Converters Feeding High Power Piezoelectric Motors - Njiende, H. D.; Fröhleke, N. (Journal of Electrical & Electronics Engineering, Australia)

Sensorless Speed Control of Permanent Magnet Synchronous Machines for Low Speed and Standstill - Kiel, J.; Bünte, A.; Beinecke, S. (Power Conversion and Intelligence Motion (PCIM 2002), Nuremberg, Germany)

Resonant Power Converter for Ultrasonic Piezoelectric Converter, Bremen Germany - Kauczor, C.; Schulte, T.; Fröhleke, N. (ACTUATOR 2002, 8th International Conference on New Actuators,)

Application, Calculation and Analysis of the Doubly Fed Longstator Linear Motor for the Wheel-on-Rail NBP Test Track - Yang, B.; Grotstollen, H. (EPE-PEMC 2002, Dubrovnik & Cavta)

PWM-Converter for Travelling Wave Type Ultrasonic Motors - Schulte, T.; Fröhleke, N. (ACTUATOR 2002, 8th International Conference on New Actuators, Bremen Germany)

Konzept zur berührungslosen Energieübertragung mit doppeltgespeistem Langstatorlinearmotor - Pottharst, A.; Grotstollen, H. (SPS/IPC/Drives 2002, Nürnberg)

Regelung doppeltgespeister Antriebe ohne mechanischen Lagesensor am Beispiel eines Linearmotors - Henke, M.; Grotstollen, H. (SPS/IPC/Drives 2002, Nürnberg)

Macfarlane, Alexander (1851–1913) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Harley, Robert (1828–1910) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Neil, Samuel (1825–1901) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Ellis, Robert Leslie (1817–59) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 1: A–H)

Bentham, George (1800–84) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 1: A–H)

Georg Misch, Logik und Einführung in die Grundlagen des Wissens. Die Macht der antiken Tradition in der Logik und die gegenwärtige Lage. hg. v. Gudrun Kühne-Bertram, Critique & Humanism Publishing House: Sofia 1999 (Studia Culturologica, Sonderheft 1999) - Peckhaus, Volker (Zeitschrift für allgemeine Wissenschaftstheorie)

José Ferreirós, Labyrinth of Thought. A History of Set Theory and Its Role in Modern Mathematics. Birkhäuser Verlag, Basel/Boston/Berlin, 1999 (Science Networks. Historical Studies, Volume 23) - Peckhaus, Volker (Studia Logica)

Norbert Hinske, Stellenindex zu „Immanuel Kant’s Logik“ (Jäsche-Logik). Studienausgabe zu Kant-Index Band 2, frommann-holzboog, Stuttgart-Bad Cannstatt, 1999 - Peckhaus, Volker (Studia Logica)

Frank-Peter Hansen, "Geschichte der Logik des 19. Jahrhunderts. Eine kritische Einführung in die Anfänge der Erkenntnis- und Wissenschaftstheorie", Königshausen & Neumann: Würzburg 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Born, Rainer, “Frege”, In: Stuart G. Shanker (Hg.), Routledge History of Philosophy, Bd. IX: Philosophy of Science, Logic and Mathematics in the Twentieth Century, Routledge: London 1996, 124–156 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rusnock, Paul, “Philosophy of Mathematics: Bolzano’s Response to Kant and Lagrange”, In: Rev. Hist. Sci. 52 (1999), No.3–4, 399–427 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kreiser, Lothar. "Gottlob Frege. Leben – Werk – Zeit", Felix Meiner Verlag: Hamburg 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Pechenkin, A. A., “Operationalism as the Philosophy of Soviet Physics: The Philosophical Background of L.I. Mandelstam and his School”, In: Synthese 124 (2000), 407–432 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rodríguez-Consuegra, Francisco, “Nominal Definitions and Logical Consequence in the Peano School”, In: Theoria. Segunda Epoca 12, no. 28 (1997), 125–137 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Waldegg, Guillermina, “Ontological Convictions and Epistemological Obstacles in Bolzano’s Geometry”, In: Science and Education 10 (2001), 409–418 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tait, W. W., “Gödel’s Unpublished Papers on Foundations of Mathematics”, In: Philosophia Mathematica (3) 9 (2001), 87–126 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stüven, Norbert, „Mathematisches Problemlösen: geschlechtsabhängig?“, In: Mitt. Math. Ges. Hamb. 16 (1997), 87–98 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sandu, Gabriel/Hyttinen, Tapani, “IF Logic and the Foundations of Mathematics”, In: Synthese 126 (2001), 37–47 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Friedman, Michael. "Reconsidering Logical Positivism", Cambridge University Press: Cambridge 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dummett, Michael. "Frege and other Philosophers", Paperback, Clarendon Press: Oxford 1996 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Linsky, Bernard. "Russell’s Metaphysical Logic", CSLI Publications: Stanford, CA 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Moore, Gregory H., “The Prehistory of Infinitary Logic: 1885–1955”, in: Maria Luisa Dalla Chiara u.a. (Hgg.), Structures and Norms in Science. Volume two of the 10th International Congress of Logic, Methodology and Philosophy of Science, Florence, Italy, August 1995, Dordrecht: Kluwer Academic Publishers 1997, 105–123 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Reichel, Hans-Christian, “How Can or Should the Recent Development in Mathematics Influence the Philosophy of Mathematics?”, in: Werner De Pauli-Schimanovich u.a. (Hgg.), The Foundational Debate. Constructivity and Complexity in Mathematics and Physics, Kluwer: Dordrecht 1995, 259–268 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Friedman, Michael, “Geometry, Construction, and Intuition in Kant and his Successors”, in: Gila Sher u.a. (Hgg.), Between Logic and Intuition. Essays in Honor of Charles Parsons, Cambridge University Press: Cambridge 2000, 186–218 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Peña, Lorenzo, “The Coexistence of Contradictory Properties in the Same Subject According to Aristotle”, In: Apeiron 32 (1999), no. 3, 203–209 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Reprint von MR 2002h:01003])

Degnan, Michael J., “What is the Scope of Aristotle’s Defense of the PNC”, In: Apeiron 32 (1999), no. 3, 243–274 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [ Reprint von MR 2002h:01005])

Koriako, Darius. "Kants Philosophie der Mathematik. Grundlagen, Voraussetzungen, Probleme", Felix Meiner Verlag: Hamburg 1999 (Kant-Forschungen; 11) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wessel, Horst. "Logik und Philosophie", Logos Verlag: Berlin 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Empfehlen oder Vorschreiben? Zur Formulierung und Legitimierung der Stilnormen in den praktischen Stilistiken nach 1945 - Ptashnyk, Stefaniya (Studia Linguistica XXI)

Wedin, M.V., “The Scope of Non-contradiction: a Note on Aristotle’s ‘Elenctic’ Proof in Metaphysics Γ 4”, In: Apeiron 32 (1999), no. 3, 231–242 - Peckhaus, Volker (Mathematical Reviews)

Peña, Lorenzo, “The Coexistence of Contradictory Properties in the Same Subject According to Aristotle”, In: Apeiron 32 (1999), no. 3, 203–209 - Peckhaus, Volker (Mathematical Reviews)

Degnan, Michael J., “What is the Scope of Aristotle’s Defense of the PNC”, In: Apeiron 32 (1999), no. 3, 243–274 - Peckhaus, Volker (Mathematical Reviews)

Thom, Paul, “The Principle of Non-contradiction in Early Greek Philosophy”, In: Apeiron 32 (1999), no. 3, 153–170 - Peckhaus, Volker (Mathematical Reviews)

Baltzly, Dirk, “Aristotle and Platonic Dialectic in Metaphysics Γ 4”, In: Apeiron 32 (1999), no. 3, 171–202 - Peckhaus, Volker (Mathematical Reviews)

Schmitz, Markus, „Erkenntnistheorie der Zahldefinition und philosophische Grundlegung der Arithmetik unter Bezugnahme auf einen Vergleich von Gottlob Freges Logizismus und platonischer Philosophie (Syrian, Theon von Smyrna u.a.)“, In: Journal for General Philosophy of Science 31 (2001), 271–305 - Peckhaus, Volker (Mathematical Reviews)

Dejnožka, Jan, “Origins of Russell’s Early Theory of Logical Truth as Purely General Truth: Bolzano, Peirce, Frege, Venn, or MacColl?”, In: Modern Logic 8 (2000/2001), nos. 3–4, 21–30 - Peckhaus, Volker (Mathematical Reviews)

Bennett, Jonathan, “Infallibility and Modal Knowledge in Some Early Modern Philosophers”, In: Mathematics and Necessity, London, 1998, Proc. Br. Acad. 103 (2000), 139–166 - Peckhaus, Volker (Mathematical Reviews)

Moore, Gregory H., “Hilbert on the Infinite: The Role of Set Theory in the Evolution of Hilbert’s Thought”, In: Historia Mathematica 29 (2002), 40–64 - Peckhaus, Volker (Mathematical Reviews [)

Den Nagel auf den Kopf treffen – Wortverbindungen mehr oder weniger fest. Bericht von der 39. Tagung des Instituts für Deutsche Sprache - Ptashnyk, Stefaniya (Deutsche Sprache: Zetischrift für Theorie, Praxis, Dokumentation. Heft 4/2002. Nachgedruckt in: (a) Sprachreport, Heft 2/2003. Hrsg. vom Institut für Deutsche Sprache. Mannheim. S. 5-12. (b) Jahresbericht des Instituts für Deutsche Sprache 2003. Mannheim, S. 30-38.)

Quasiparticle calculations for point defects on semiconductor surfaces - Hedström, Magnus; Schindlmayr, Arno; Scheffler, Matthias (Physica Status Solidi B)
We discuss the implementation of quasiparticle calculations for point defects on semiconductor surfaces and, as a specific example, present an ab initio study of the electronic structure of the As vacancy in the +1 charge state on the GaAs(110) surface. The structural properties are calculated with the plane‐wave pseudopotential method, and the quasiparticle energies are obtained from Hedin's GW approximation. Our calculations show that the 1a″ vacancy state in the band gap is shifted from 0.06 to 0.65 eV above the valence‐band maximum after the self‐energy correction to the Kohn‐Sham eigenvalues. The GW result is in close agreement with a recent surface photovoltage imaging measurement.

Utility and Universality versus Utility and the General Good - Hagengruber, Ruth Edith (Philosophie und Wissenschaft. Tagungsakten zum 70. Geburtstag von Wolfgang H. Müller)

Philosophie und Wissenschaft. Tagungsakten zum 70. Geburtstag von Wolfgang H. Müller

An OCL Extension for Real-Time Constraints - Flake, Stephan; Müller, Wolfgang (Advances in Object Modelling with the OCL)
The Object Constraint Language (OCL) was introduced to support the specification of constraints for UML diagrams and is mainly used to formulate invariants and operation pre- and postconditions. Though OCL is also applied in behavioral diagrams, e.g., as guards for state transitions, it is currently not possible to specify constraints concerning the dynamic behavior and timing properties of such diagrams. This article discusses OCL’s application for the dynamic behavior of UML Statechart diagrams and presents an OCL extension for specification of state-oriented time-bounded constraints.We introduce operations to extract state configurations from diagrams and define additional predicates over states and state configurations. The semantics of our OCL extension is given by employing time-bounded Computational Tree Logic (CTL) formulae. An example of a flexible manufacturing system with automated guided vehicles demonstrates the application of our extension.
Keywords: Model Check Temporal Logic Object Constraint Language Execution Path Kripke Structure